2019
DOI: 10.1111/mve.12373
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in the tick Argas japonicus (Acari: Argasidae) with a focus on Rickettsia pathogens

Abstract: The soft tick Argas japonicus mainly infests birds and can cause human dermatitis; however, no pathogen has been identified from this tick species in China. In the present study, the microbiota in A. japonicus collected from an epidemic community was explored, and some putative Rickettsia pathogens were further characterized. The results obtained indicated that bacteria in A. japonicus were mainly ascribed to the phyla Proteobacteria, Firmicutes and Actinobacteria. At the genus level, the male A. japonicus har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Currently, Proteobacteria is the broadest phylum in the Bacteria domain [37]. Some of the tick species that have shown dominance of this phylum in their microbiota are Argas japonicus in China (42-97%) [38], Hyalomma dromedarii in Saudi Arabia (98%) [39], Dermacentor marginatus and D. reticulatus in Slovakia (60%) [40], D. marginatus (97%), Haemaphysalis punctata (98%), Ixodes ricinus (88%), and Rhipicephalus sanguineus sensu lato (99%) in Spain [41], and I. scapularis in Massachusetts and Texas, USA (73-100%; [8]).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, Proteobacteria is the broadest phylum in the Bacteria domain [37]. Some of the tick species that have shown dominance of this phylum in their microbiota are Argas japonicus in China (42-97%) [38], Hyalomma dromedarii in Saudi Arabia (98%) [39], Dermacentor marginatus and D. reticulatus in Slovakia (60%) [40], D. marginatus (97%), Haemaphysalis punctata (98%), Ixodes ricinus (88%), and Rhipicephalus sanguineus sensu lato (99%) in Spain [41], and I. scapularis in Massachusetts and Texas, USA (73-100%; [8]).…”
Section: Resultsmentioning
confidence: 99%
“…While only a few Rickettsia species have been reported from soft ticks (Duh et al, 2010;Duron et al, 2018;Hornok et al, 2019;Milhano et al, 2014;Moreira-Soto et al, 2017;Sánchez-Montes et al, 2016;Tahir et al, 2016;Yan et al, 2019), in this study we identified two novel Rickettsia species in soft tick Ornithodoros species from North Africa. The MLST of four gene fragments fulfills the criteria usually used to designate new Rickettsia species (e.g.…”
Section: Discussionmentioning
confidence: 63%
“…and Ornithodoros spp., but also the R. wissemanii, R. nicoyana, R. lusitianiae and undetermined species, which are known only from a few Ornithodoros and Argas species (Duh et al, 2010;Duron et al, 2018;Hornok et al, 2019;Milhano et al, 2014;Moreira-Soto et al, 2017;Sánchez-Montes et al, 2016;Tahir et al, 2016;Yan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To date, few NGS studies have investigated the bacterial microbiota associated with soft tick species [18][19][20], and, to our knowledge, the present work constitutes the first NGS study of bacterial microbiota in Ornithodoros maritimus. The results reveal some similarities to the microbiota of hard tick species.…”
Section: Discussionmentioning
confidence: 99%
“…among microbiota and between host and microbiota) may provide tools for the control of tick-borne diseases [15,16]. Although relatively few NGS studies have examined tick microbiomes to date, most of these focus on bacterial communities sheltered by hard ticks (family: Ixodidae) [7,16,17], and little is known about these communities in soft ticks (family: Argasidae) [18][19][20]. These NGS studies have shown that tick microbiota include a remarkable diversity of endosymbiotic, commensal and pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%